2022
DOI: 10.3390/diagnostics12010148
|View full text |Cite
|
Sign up to set email alerts
|

Application of Highly Flexible Adaptive Image Receive Coil for Lung MR Imaging Using Zero TE Sequence: Comparison with Conventional Anterior Array Coil

Abstract: (1) Background: Highly flexible adaptive image receive (AIR) coil has become available for clinical use. The present study aimed to evaluate the performance of AIR anterior array coil in lung MR imaging using a zero echo time (ZTE) sequence compared with conventional anterior array (CAA) coil. (2) Methods: Sixty-six patients who underwent lung MR imaging using both AIR coil (ZTE-AIR) and CAA coil (ZTE-CAA) were enrolled. Image quality of ZTE-AIR and ZTE-CAA was quantified by calculating blur metric value, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, the work failed to disclose the number of AIR coil elements used. In contrast, Bae et al [ 27 ] described the comparison of a 30-channel ‘blanket’ AIR coil to a conventional 16-channel conventional anterior array for ZTE imaging of the lung, which, as expected, indicated increased image quality due in part to the almost doubling in coil elements in the AIR compared to the conventional coil. The unique contribution of this work is the qualitative and quantitative evaluation of a pre-clinical, novel (i.e., AIR) RF coil technology specifically designed to address one of the most challenging anatomic sites for the MR imaging of radiation therapy patients in treatment position, namely the head and neck.…”
Section: Discussionmentioning
confidence: 97%
“…However, the work failed to disclose the number of AIR coil elements used. In contrast, Bae et al [ 27 ] described the comparison of a 30-channel ‘blanket’ AIR coil to a conventional 16-channel conventional anterior array for ZTE imaging of the lung, which, as expected, indicated increased image quality due in part to the almost doubling in coil elements in the AIR compared to the conventional coil. The unique contribution of this work is the qualitative and quantitative evaluation of a pre-clinical, novel (i.e., AIR) RF coil technology specifically designed to address one of the most challenging anatomic sites for the MR imaging of radiation therapy patients in treatment position, namely the head and neck.…”
Section: Discussionmentioning
confidence: 97%
“…Flexible coils have been tested in humans and are nowadays available in clinical settings, as reported, for instance, in the papers by Bae et al [ 69 ], Wang et al [ 70 ] and Zamarayeva et al [ 67 ]. Figure 11 shows an example of a custom coil array.…”
Section: Noveltiesmentioning
confidence: 99%
“…Bae et al [ 69 ] showed the performance of a highly flexible adaptive receive (AIR) anterior array coil for lung MRI using a zero echo time (ZTE) sequence at 3 T evaluated and compared with that of a conventional anterior array (CAA) coil. According to the results obtained from 66 patients, the AIR array coil provided a superior SNR, image quality and sharpness compared with the CAA coil; in addition, the combination of ZTE and AIR coils offered a better diagnostic capability, providing higher sensitivity and accuracy for lesion detection in cases of sub-centimeter nodules, emphysema and/or cysts than a ZTE-CAA coil.…”
Section: Noveltiesmentioning
confidence: 99%
“…Supine positioning, though, could also be advantageous for screening through improved comfort and ease of setup. Additionally, while previous investigations of supine breast MRI relied on rigid body, cardiac, or prototype coils, recently available flexible coils could further facilitate a comfortable and efficient exam 11,12,14,15 …”
mentioning
confidence: 99%
“…Additionally, while previous investigations of supine breast MRI relied on rigid body, cardiac, or prototype coils, recently available flexible coils could further facilitate a comfortable and efficient exam. 11,12,14,15 Acquisition of DWI of the breasts with supine positioning has been rarely investigated, 16 but DWI of the breasts with prone positioning has been extensively investigated, with several advanced DWI methods providing improvements in image quality. [17][18][19][20][21][22][23][24] In particular, multishot DWI (msDWI) methods, which can reduce distortion and improve resolution, have been assessed in the breasts in previous studies.…”
mentioning
confidence: 99%